A new expansive two-open-doors laminoplasty for multilevel cervical spondylotic myelopathy: technical report and follow-up results - Aluizio Augusto Arantes Júnior; Geraldo Alves da Silva Junior; José Augusto Malheiros; Fernando Flavio Gonçalves; Marcelo Magaldi; Erica Santiago; Arthur Adolfo Nicolato; Sebastião Nataniel Silva Gusmão (Arquivos de Neuro-Psiquiatria)
The laminoplasty technique was devised by Hirabayashi in 1978 for patients diagnosed with multilevel cervical spondylotic myelopathy. Objective: To describe an easy modification of Hirabayashi’s method and present the clinical and radiological results from a five-year follow-up study. Method and Results: Eighty patients had 5 levels of decompression (C3-C7), 3 patients had 6 levels of decompression (C2-T1) and 3 patients had 4 levels of decompression (C3-C6). Foraminotomies were performed in 23 cases (27%). Following Nurick`s scale, 76 patients (88%) improved, 9 (11%) had the same Nurick grade, and one patient worsened and was advised to undergo another surgical procedure. No deaths were observed. The mean surgery time was 122 min. Radiographic evaluation showed an increase in the mean sagittal diameter from 11.2 mm at pretreatment to 17.3 mm post surgery. There was no significant difference between pretreatment and post-surgery C2-C7 angles. Conclusions: This two-open-doors laminoplasty technique is safe, easy and effective and can be used as an alternative treatment for cases of multilevel cervical spondylotic myelopathy without instability.